Molecular structure and vibrational and chemical shift assignments of 5-(2-Hydroxyphenyl)-4-(p-tolyl)-2,4-dihydro-1,2,4-triazole-3-thione by DFT and ab initio HF calculations - Dincer, Muharrem; Avci, Davut; Sekerci, Mehmet; Atalay, Yusuf (Springer, 2008)
The molecular geometry, vibrational frequencies, gauge including atomic orbital (GIAO) H-1 and C-13 chemical shift values and several thermodynamic parameters of 5-(2-Hydroxyphenyl)-4-(p-tolyl)-2,4-dihydro-1,2,4-triazole-3-thione in the ground state have been calculated by using the Hartree-Fock (HF) and density functional method (DFT/B3LYP) with 6-31G(d), 6-31 + G(d,p) and LANL2DZ basis sets. The results of the optimized molecular structure are presented and compared with the experimental X-ray diffraction. The computed vibrational frequencies are used to determine the types of molecular motions associated with each of the experimental bands observed. Also, calculated H-1 chemical shift values compared with the experimental ones. The data of the title compound display significant molecular structure and IR, NMR analysis provide the basis for future design of efficient materials having the of 1,2,4-triazole core.
Keywords: 5-(2-Hydroxyphenyl)-4-(p-tolyl)-2,4-dihydro-1,2,4-triazole-3-thione; DFT; HF; GIAO; H-1; C-13 NMR; IR spectra; structure elucidation; vibrational assignment